2021
DOI: 10.3390/biomedicines9091100
|View full text |Cite
|
Sign up to set email alerts
|

Wilson’s Disease: Facing the Challenge of Diagnosing a Rare Disease

Abstract: Wilson disease (WD) is a rare disorder caused by mutations in ATP7B, which leads to the defective biliary excretion of copper. The subsequent gradual accumulation of copper in different organs produces an extremely variable clinical picture, which comprises hepatic, neurological psychiatric, ophthalmological, and other disturbances. WD has a specific treatment, so that early diagnosis is crucial to avoid disease progression and its devastating consequences. The clinical diagnosis is based on the Leipzig score,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 158 publications
(194 reference statements)
1
17
0
1
Order By: Relevance
“…In the work carried out on a 3D culture of hepatocytes, it was also shown that the release of AST into the culture medium is especially high when cells are exposed to preparations, the toxic effect of which is related with mitochondrial dysfunction [ 67 ]. At the same time, our data are consistent with the information that in Wilson–Konovalov’s disease characterized by the accumulation of excess copper amounts in liver cells, a predominant increase in AST activity is recorded in the blood serum, and therefore the AST/ALT ratio exceeding 2 is considered one of the clinical indicators of this pathology [ 73 , 74 ]. In addition, the fact that the appearance of mitochondrial enzymes in blood serum under pathological conditions is usually observed later than cytoplasmic enzymes [ 75 ] may explain a significant AST activity growth in the culture medium at later stages of incubation with CuAc 2 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In the work carried out on a 3D culture of hepatocytes, it was also shown that the release of AST into the culture medium is especially high when cells are exposed to preparations, the toxic effect of which is related with mitochondrial dysfunction [ 67 ]. At the same time, our data are consistent with the information that in Wilson–Konovalov’s disease characterized by the accumulation of excess copper amounts in liver cells, a predominant increase in AST activity is recorded in the blood serum, and therefore the AST/ALT ratio exceeding 2 is considered one of the clinical indicators of this pathology [ 73 , 74 ]. In addition, the fact that the appearance of mitochondrial enzymes in blood serum under pathological conditions is usually observed later than cytoplasmic enzymes [ 75 ] may explain a significant AST activity growth in the culture medium at later stages of incubation with CuAc 2 .…”
Section: Resultssupporting
confidence: 91%
“…Substitution of zinc in the catalytic centers of the enzyme also explains the reduction in the ALP activity level of the blood serum observed in patients with Wilson–Konovalov disease, especially when it manifests itself in the fulminant form accompanied by extensive necrosis of the liver [ 77 , 78 ]. In the case of this disease characterized by the accumulation of excessive amounts of copper in the liver, a decrease the ALP activity in serum does not reflect the degree of hepatocellular damage but is one of the diagnostic signs indicating the toxic effect of copper [ 73 , 74 , 79 ]. A similar effect of copper preparations on ALP activity was also previously described; however, in contrast to our results, in these studies, only complexes of myo-inositol hexakisphosphate with Cu (II) ions but not free copper ions had an inactivating effect (the enzyme activity decreased by 99%) [ 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…A score of 4 and more points confirms WD. Unfortunately, the assessment based on the Leipzig scoring system does not always provide evident conclusions [ 67 , 68 ] and although genetic testing is currently more available, some patients still cannot obtain it. The criteria for WD diagnosis included in the Leipzig score are presented in Table 1 .…”
Section: Diagnostic Approach To Patients With Wilson’s Disease Suspicionmentioning
confidence: 99%
“…As it is known, ceruloplasmin levels are reduced in Wilson disease, in which copper cannot be involved into ceruloplasmin in the liver due to defects in the copper-transporting ATPase 2. Serum ceruloplasmin is the major diagnostic criteria for Wilson disease [ 45 , 46 ]. The alteration in the degree of copper and ceruloplasmin oxidase activity in human amniotic fluid from 20 weeks’ gestation to term was detected.…”
Section: Discussionmentioning
confidence: 99%